Etude des amibes marines et de leurs interactions avec les vibrios pathogènes d’huître - Robino, Etienne (Université de Montpellier, 2019)
Free living amoebae inhabit aquatic environments and use phagocytosis of bacteria for their nutrition. According to the hypothesis of coincidental evolution of virulence, the cellular and molecular mechanisms of phagocytosis being preserved from amoebae to the immune cells of animals, the predation exerted by amoebae could favor the emergence of pathogenic bacteria resistant to phagocytosis. Since 2008, Crassostrea gigas oysters have suffered from over-mortality in France. This poly-microbial disease involves the Herpes OsHV-1 μvar virus which causes an immunosuppression of oysters that are then colonized by various opportunistic pathogenic bacteria including vibrios inducing the death of the animal. V. tasmaniensis LGP32 is a facultative intracellular pathogen of oyster hemocytes that resists phagocytosis and destroys hemocytes using different virulence factors. We have therefore undertaken to study the interactions between marine amoebae of the oyster environment and the vibrios in order to verify if some mechanisms of virulence could also play a role in this type of interactions. By performing field sampling, we demonstrated that the interaction between vibrios and amoebae is ecologically realistic and observed a low diversity of heterotrophic protists near the oyster tables of the Thau Lagoon compared to other less anthropogenic environments. Functional studies between LGP32 and the amoeba Vannella sp. AP1411 showed that LGP32 is able to resist amoeba predation involving certain virulence factors such as Vsm metalloprotease and CopA P-ATPase copper efflux pump which are also involved in the interaction of LGP32 with oysters. In contrast, other virulence factors implicated in the oyster are not involved in amoeba-predation resistance indicating that some factors are involved in interactions with various hosts while others would be involved in more specific interactions. Les amibes libres dans les environnements aquatiques utilisent la phagocytose des bactéries pour leur nutrition. Selon l’hypothèse de ...